Labours of Representation: A Bosnian Workers’ Movement and the Possibilities of Collaborative Graphic Ethnography - Gilbert, Andrew; Kurtović, Larisa (Anthropologica)

(untitled) (University of Victoria, 2022)
Collaborative graphic ethnography can generate new ways of identifying, materializing, and documenting political possibility in what otherwise seems like an overdetermined world, and in doing so, offers a model for practicing anthropology differently. We come to these insights through our work in the embattled Bosnian detergent factory “Dita,” located on the outskirts of the post-industrial city of Tuzla, whose workers scored an unprecedented victory when they managed to preserve their factory and restart production despite the threat of bankruptcy and liquidation. In researching and telling the story of their struggle and victory through this innovative format, we build upon the historical popularity of comics in former Yugoslavia, as well as contemporary experimentation with the form among anti-corruption activists in Bosnia-Herzegovina. We explore ethnographic and political affordances of sequential art and the graphic form for an engaged or activist anthropology, including its capacity to visualize and materialize the immaterial and overlooked aspects of politics, mitigate anthropology’s extractivist tendencies, enlist the imagination and participation of readers in directions both hoped for and unanticipated, and engage and animate multiple local and international publics.